2015
DOI: 10.1118/1.4938577
|View full text |Cite
|
Sign up to set email alerts
|

Medical image segmentation via atlases and fuzzy object models: Improving efficacy through optimum object search and fewer models

Abstract: Although multiple models per object can usually improve segmentation efficacy, the optimum object search has shown to reduce the number of required models. The efficiency gain of FOSM over SOSM-S motivates its use for interactive applications and studies with large image data sets. FOSM and SOSM impose different degrees of shape constraints from the model, making one approach more suitable than the other, depending on contrast. This suggests the use of hybrid models that can take advantage from the strengths o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 40 publications
0
30
0
2
Order By: Relevance
“…Methods based on PAs estimate a prior probabilistic map P where each voxel has a prior probability of belonging to a given object independent of its value in the image . The construction of P requires deformable image registration to place object masks from X on to a common coordinate system — the domain of a template (reference 3D image) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Methods based on PAs estimate a prior probabilistic map P where each voxel has a prior probability of belonging to a given object independent of its value in the image . The construction of P requires deformable image registration to place object masks from X on to a common coordinate system — the domain of a template (reference 3D image) .…”
Section: Introductionmentioning
confidence: 99%
“…In Grau et al, for instance, the authors binarize P , apply morphological operations, and estimate seeds for object delineation by watershed transform. Phellan et al in turn have demonstrated that if we acknowledge errors in registration, the accuracy of PAs may be significantly improved as long as a local search for the object is performed with the model. For this purpose, its statistical object model, named SOSM‐S, translates over the test image in the reference space for more accurate object localization and delineation by using the Image Foresting Transform (IFT) algorithm .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Image segmentation is according to the certain rules to divide the image into the several mutually disjoint that has certain properties of the area, the attention to a part extracted from the image of the further research and analysis and processing [1][2]. The result of image segmentation is the basis of the image feature extraction and the recognition of image understanding, the study of image segmentation has been a hot spot and focus in the study of the digital image processing techniques that makes the subsequent image analysis and image segmentation to identify the amount of data to be processed by the advanced stage of processing, such as greatly reduced, and retain information about the image structure characteristics at the same time [3][4].…”
Section: Introductionmentioning
confidence: 99%